A Heterostructured Sulfonated CNT/Sulfur/CNT Cathode for Promoting the Binary Conversion of Polysulfides in Lithium‐Metal Batteries. Issue 2 (6th December 2021) - Li, Min; Zhou, Xianxian; Liu, Xiaoxiao; Chen, Liang; Zhang, Ding; Xu, Shoudong; Duan, Donghong; Yuan, Qinbo; Ling, Lixia; Liu, Shibin
Abstract: The shuttle effect of lithium polysulfides (LiPS) and sluggish redox kinetics hinder the commercialization of lithium‐sulfur (Li−S) batteries. Herein, we design a lightweight and multifunctional multi‐walled carbon nanotube (CNT)/sulfur/lithiated sulfonated CNT (M/S/M‐SO3 Li) electrode as energy storage devices. Flexible CNT films ensure continuously electron/ion transmission and serve as LiPS shielding layer. Moreover, guided by DFT and experimental results, SO3 groups exert a vital adsorption effect toward sulfur species but not NH4 + groups. The SO3 groups can not only employ as LiPS immobilizer by Li−O bands between LiPS and SO3, but also serve as multifunctional electrocatalyst to propel LiPS conversion via generating thiosulfate and polythionate and Li2 S decomposition by reducing reaction overpotential. As expected, M/S/M‐SO3 Li electrode exhibits prominent rate capability (723.5 mAh g −1 at 5 C), high sulfur loading (7.09 mAh cm −2 at 5.0 mg cm −2 sulfur), favorable anti‐self‐discharge capabilities (rest for 72 h at 0.5 C with 2.17 %). Abstract : Multifunctional electrocatalyst : The M/S/M‐SO3 Li cathode solves the shuttle effect in two ways. On the one hand, it has strong chemical interaction with polysulfide via Li−O bonds, which will inhibit the shuttling of polysulfide. On the other hand, it accelerates the polysulfide catalyst‐conversion process via fast reaction kinetics. This presented cathode strategy will contribute to conducting the design of multifunctional and lightweight electrodes.